Hibridismo no mercado da música e a articulação das identidades - Michel Nicolau Netto (Ciências Sociais Unisinos)
In a situation of globalization, national identity comes to be produced in the global space, where national and non-national agents operate. In this scenario, national identity does not become less important, but, on the contrary, widens its meaning and embraces other cultural dynamics, rather than the national culture alone. It is this enlargement of mean- ing that allows the contemporary simultaneousness of national identity and diversity. At the same time, as identities are perceived as opposed to the standardization suppos- edly caused by globalization, some of them acquire the value of difference and become negotiable in the global market of symbols. This process is clearly noticed at the level of social relations, which are analyzed here on the basis of descriptions of musicians found in catalogues of a World Music international trade fair. These descriptions show that social actors can now articulate identities hoping for a symbolic gain. The use of hybridity means this articulation. However, the possibilities of gains are not equally distributed.